The Strategi Promosi Hapsari Scarf Melalui Media Sosial Instagram - Meilani Tri Hapsari (KOMVERSAL, 2020)
ABSTRACT Promotion Strategy for Hapsari Scarf through Instagram Social Media. This study aims to determine the form of marketing communication and sales promotion carried out by Hapsari Scarf through Instagram social media. The research methodology used is qualitative research by describing the marketing communication and sales promotion of Hapsari Scarf on social media Instagram. The research data was obtained from Hapsari Scarf's Instagram account. The research subject is focused on the Instagram account which contains the substance of the Hapsari Scarf promotional strategy. The results showed that the form of marketing communication carried out by Hapsari Scarf through social media Instagram is advertising, personal selling, promotion, and publication. From the findings in the field, it was also found that the promotion strategy carried out by Hapsari Scarf was sales promotion, namely by means of premiums, sweep stakes, contests, and free sample distribution. There is also a sales promotion method that will be carried out in the future, namely by holding shopping coupons and endorsements using national-scale artists. Keywords: promotion, marketing communications, sales promotion, social media, Instagram ABSTRAK Strategi Promosi Hapsari Scarf Melalui Media Sosial Instagram. Penelitian ini bertujuan untuk mengetahui bentuk komunikasi pemasaran dan sales promotion yang dilakukan Hapsari Scarf melalui media sosial Instagram. Metodologi penelitian yang digunakan adalah penelitian kualitatif dengan memaparkan komunikasi pemasaran dan sales promotion Hapsari Scarf pada media sosial Instagram. Data penelitian diperoleh dari akun Instagram milik Hapsari Scarf. Subjek penelitiannya difokuskan pada akun Instagram yang memuat substansi strategi promosi Hapsari Scarf. Hasil penelitian menunjukkan bentuk komunikasi pemasaran yang dilakukan Hapsari Scarf melalui media sosial Instagram adalah periklanan, personal selling, promosi, dan publikasi. Dari hasil temuan di lapangan juga ditemukan data bahwa strategi promosi yang dilakukan Hapsari Scarf adalah dengan sales promotion yaitu dengan cara premiums, sweep stakes, contest, dan pembagian sampel gratis. Ada pun metode sales promotion yang akan dilakukan untuk selanjutnya adalah dengan mengadakan kupon belanja dan endorse menggunakan artis berskala Nasional.